2015
DOI: 10.1016/j.chb.2015.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on Facebook practices: A comparative study of college students in Namibia and the United States

Abstract: Facebook has been adopted in many countries with over 80% of its user-base being outside of the US and Canada. Yet, despite this global dominance, not much is understood of Facebook usage by individuals in nonwestern cultures. A cross-cultural study was conducted with undergraduate students in the United States and Namibia to examine Facebook use. The study used a mixed method of online surveys and focus groups in both countries. The research examined issues such as motivations for use, friendships, privacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…preferred more public expressions of closeness diffused on Facebook. Additionally, researchers who conducted focus groups in the U.S. and Namibia, found that Namibian college students, who have less individualistic values, were more likely to view Facebook as a tool for privately chatting with friends than U.S. college students (Peters, Winschiers-Theophilus, & Mennecke, 2015). In the same vein, researchers found that lower individualism was correlated with concerns about privacy which was associated with preferring the use of instant messenger over other methods of communication (Lowry, Cao, & Everard, 2010).…”
Section: Individualism and Facebook Network Sizementioning
confidence: 99%
“…preferred more public expressions of closeness diffused on Facebook. Additionally, researchers who conducted focus groups in the U.S. and Namibia, found that Namibian college students, who have less individualistic values, were more likely to view Facebook as a tool for privately chatting with friends than U.S. college students (Peters, Winschiers-Theophilus, & Mennecke, 2015). In the same vein, researchers found that lower individualism was correlated with concerns about privacy which was associated with preferring the use of instant messenger over other methods of communication (Lowry, Cao, & Everard, 2010).…”
Section: Individualism and Facebook Network Sizementioning
confidence: 99%
“…Some researchers argue that all digital natives do not share the same level of competencies and knowledge about technologies. They may differ according to habits and access to technologies 2,[4][5][6][9][10][11][12][13][14] . Even if one grows up with opportunities to use digital media, it does not mean that one will actually take advantage of this favorable context and use them.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has also rapidly changed college students' reading practices from linear printed materials to nonlinear on‐screen reading (Huang et al., ; Lin, Yen, Hsu, Jin, & Lin, ). More specifically, social media websites (e.g., Facebook) have welcomed college‐age users to connect to the world through their networks (Peters, Winschiers‐Theophilus, & Mennecke, ). To date, nearly 99% of U.S. college students use Facebook (Goel, ; Jones & Fox, ; Junco, ; Matney & Borland, ).…”
mentioning
confidence: 99%